The Urgency of Character Education Based on Prophetic Pedagogy: An Approach to Overcoming Students’ Moral Crisis - Abdul Basith, Fardan; Hilman Rasyid; Euis Erha Rohmah; Aan Hasanah; Bambang Samsul Arifin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Education is the main pillar in shaping the quality of human resources. Phenomena such as increasing deviant behavior, lack of responsibility, fading spirit of mutual cooperation, and declining honesty and social ethics are a reflection that the education system has not fully succeeded in shaping a complete human being. This crisis shows that education that only focuses on academic aspects is not enough to produce individuals with noble morals. The urgency of character education is increasingly felt in the context of modern life which is marked by the rapid flow of globalization, the development of information technology, and the rapid flow of instant culture that tends to deny noble values ​​and local wisdom. Various studies have shown that character education can have a positive impact on students' behavior, both in the school environment and in society. Character education encourages students to internalize good values ​​such as responsibility, discipline, cooperation, and respect for differences. These values ​​are important provisions in building a harmonious social life, as well as forming a generation that has integrity and healthy competitiveness. Therefore, character education not only functions as an instrument for forming individual personality, but also as an instrument of social transformation in order to create a civilized social order.